Pengaruh persepsi profesi guru dan lingkungan keluarga terhadap minat menjadi guru mahasiswa Pendidikan Administrasi Perkantoran - Nur Mahalani; Cicillia Dyah Sulistyaningrum Indrawati; Subroto Rapih (Politeknik Kampar, 2023)
This study aims to investigate: 1) the effect of perceptions of the teaching profession on interest in becoming a teacher; 2) the effect of family environment on interest in becoming a teacher; and 3) the effect of perceptions of the teaching profession and family environment on interest in becoming a teacher of PAP students. This research is a quantitative study with a survey method with a population of 241 PAP students class of 2019-2021. The sampling technique used proportionate stratified random sampling with a sample of 150 students. The results showed that: 1) there is a positive and significant effect of the perception of the teaching profession on interest in becoming a teacher. This is evidenced by tcount> ttable (1.997>1.976) at a significance level of 5%; 2) there is a positive and significant influence of the family environment on interest in becoming a teacher. This is evidenced by tcount> ttable (14.647> 1.976) at the 5% significance level; and 3) there is a positive and significant influence of the perception of the teaching profession and the family environment on the interest in becoming a teacher of PAP students. This is evidenced by Fcount> Ftable (111.785> 3.06) at the 5% significance level.